Aktivitas antibateri sediaan hand and body lotion dari ekstrak etanol daun binahong (Anredera cordifolia (Ten.) Steenis) terhadap bakteri Staphylococcus aureus - Dominica, Dwi; Anisah, Saskia; Wibowo, Risky Hadi; Shufyani, Fahma (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background: Formulation is an activity to design the composition of the active ingredients and additional ingredients to make specific preparations. One of the herbal plants that can be formulated in hand and body lotion is binahong leaves (Anredera cordifolia (Ten.) Steenis), which contain secondary metabolites such as flavonoids, saponins, alkaloids, and tannins. These secondary metabolites function as antibacterials. Gram-positive bacteria often cause skin problems, such as Staphylococcus aureus. This study aimed to determine the antibacterial activity of 5%, 7.5%, 10%, 12.5%, and 15% binahong leaf extract hand and body lotion against S. aureus bacteria. This research was conducted experimentally, including an examination of the physical quality of the preparation (organoleptic, homogeneity, pH, spreadability, and adhesion). This Method research is an experimental study, including collecting samples, making kepok banana heart calyx juice with concentrations of 2%, 4% and 6%, ointment evaluation tests and cut wound healing activity tests on white mice which were grouped into five groups with each group consisting of of 5 mice. Statistical analysis included a one-way ANOVA test to see whether there was a significant difference between concentrations and wound healing in white male mice. The results showed that binahong leaf extract could be formulated into hand and body lotion preparations because it has a homogeneous composition, a pH range of 4.8-5.1, spreadability of 5.7-6.0 cm, and adhesion of 2.16-2.49 seconds. Hand and body lotion preparations with 10% binahong leaf extract have the best physical quality. All formulations of binahong leaf extract hand and body lotion in this study could inhibit the growth of S. aureus with weak inhibition, and the best formula for inhibiting the growth of S. aureus was 15% binahong leaf extract hand and body lotion having a diameter of inhibition zone 2.575 m.